Group Contests with Internal Conflict and Power Asymmetry - Jay Pil Choi; Subhasish M. Chowdhury; Jaesoo Kim (Center for Economic Studies and ifo Institute (CESifo), 2014)
We investigate situations in which players make costly contributions as group members in a group conflict, and at the same time engage in contest with fellow group members to appropriate the possible reward. We introduce within group power asymmetry and complementarity in members' efforts, and analyze how each group's internal conflict in-fluences its chance of winning in the external conflict. We find that a more symmetric group may expend more effort in external conflict when the (common) collective action technology exhibits a high degree of complementarity. Furthermore, depending on the degree of complementarity, the stronger player's relative contribution to external conflict may be higher in a more asymmetric group and, as a result, it is possible for the weaker player to earn a higher payoff. In absence of any complementarity, the rent-dissipation is non-monotonic with the within-group power asymmetry.
Keywords: C72; D72; D74; H41; 330; conflict; collective action; group contest; asymmetry